Political Budget Cycles Revisited: Testing the Signalling Process - Israel Garcia; Bernd Hayo (Philipps-University Marburg, School of Business and Economics, 2020)
A widespread view in the 'political budget cycles' literature is that incumbent politicians seek to influence voters' perceptions of their competence and/or preferences by using the composition of the fiscal budget as a signalling tool. However, little is known about whether voters actually receive and perceive the signal in that way. To empirically assess the relevance of the signalling channel at the municipal level, we conducted a survey among 2,000 representative German citizens in 2018. Only a small fraction of voters feel well-informed about the fiscal budget signal and use the information it contains to decide whether to vote for the incumbent politician. Persons paying more attention to the signal sent by local politicians live in smaller municipalities, are more satisfied with their economic situation, are more educated, and do not feel that they are being electorally targeted. Our analysis suggests that the municipal voting decision, at least in Germany, is a more complex process than is commonly assumed in political budget cycle models.
Keywords: E62; D83; H70; H72; 330; Political budget cycles; Signalling mechanism; Local government; Fiscal policy; Representative population survey; Germany